AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN PADA MASJID DARUL FALAH KECAMATAN PONTIANAK KOTA - Lestary, Dini; Muniroh, Syrly (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2023)
Purpose: This research was conducted on the Darul Falah Mosque in Pontianak Kota District. This study aims to find out how the accountability and transparency of the management of financial reports at the Darul Falah Mosque. This research was conducted with qualitative methods. Design/methodology/approach: Data collection was carried out by interviews and information retrieval from the financial reports of the Darul Falah Mosque in Pontianak Kota District. Data sources were obtained from the treasurer and secretary of the Darul Falah Mosque. Research Findings: Based on the results of the research conducted, it shows that the treasurer of the Darul Falah Mosque has not fully implemented accountability and transparency because there are several principles of accountability and transparency that have not been implemented by the administrators of the Darul Falah Mosque but the management of financial reports at the mosque has used modern methods, namely all financial reports are recorded. using a computer and this method has been applied for a long time. Contribution/Originality/Novelty: accountability and transparency in Darul Falah Mosque